Evaluation on the Application of Pseudommonas fluorescens and Chitosan Against Soybean Mosaic Virus - Andayanie, Wuye Ria; dinurani, Praptiningsih Gamawati; Lukito, Martin (Molekul, 2024)
ABSTRACT. Soybean mosaic virus (SMV) causes a decrease in soybean [Glycine max (Leguminosae) Merril] production. Activity of the Pseudomonas fluorescens (Pseudomonadaceae ) and chitosan can increase soybean plant resistance to SMV and stimulate plant growth. Therefore, The study aimed to evaluate the effect of increasing salicylic acid and total phenol contents on the biological control activity of P. fluorescens and chitosan against SMV. This study used two soybean varieties (Wilis and Anjasmoro) and three lines (GK/Mlg 3288-7-11, W/PI 200.485-7-14, and GK/PI200.485-7-2). Treatment using seed encapsulation with P. fluorescens combined with chitosan on the Wilis variety was the highest percentage of the total phenolic and salicylic acid content. In addition, Applying P. fluorescens with chitosan suppresses disease incidence on the Wilis variety and GK/Mlg 3288-7-11 line. Moreover, the ELISA absorbance value was low (0.182−0.224) and reacted negatively with no symptoms. Therefore, applying P. fluorescens combined with chitosan on the GK/Mlg 3288-7-11 line could be developed as the candidate variety for SMV control in the endemic soybean plant area. Keywords: Disease incidence, ELISA, induce systemic resistance, secondary metabolites, soybean.